Avaliando uma proposta de ensino para crianças que apresentam dificuldades em leitura e escrita - Martimiano, Thaís Helena Tadiotto (2010)
Reading and writing skills are essential for the growing of population. The official results from performance evaluation programs (SARESP), which is applied once a year, show that many students on the fourth grade of Junior School misinterpret and are not able to write texts. The Behavior Analysis, through the researches based on incentive equivalence model, has been showing promising results related to reading teach. New studies, focused on writing repertoire, will be able to bring results which can contribute with teachers to reach in a more efficient way the necessary conditions for illiteracy eradication. The objective of this study was to evaluate the consequences of a teaching program, applied via the under the name Mestre ®, for the writing and reading skills of eight students from a Junior School located at a suburb on São Paulo Northern area. The students were chosen by the respective responsible teachers, based on the criteria of lowest levels of scoring performance established by the school. The procedure for data collection started with the evaluation of the initial repertoire of each student (before training). The training was based on the connection of words (spoken and written) and pictures, connection of words (spoken and written) and letters and connection among syllables and letters, focusing words with simples and complex syllables, testing expressive reading and manual writing of teaching words. It was evaluated general reading and writing skills via the application of tests of expressive reading and manual writing of new words and phrases, containing learned and not learned words. The evaluation of initial repertoire test was applied for the again afterwards, and after 27 days of the training end, the test for performance maintenance review was applied. The results show that the majority of the students started to read, beyond trained words, new words and phrases; and that all the students were in a generalization writing process, confirming that the procedure and methodology were effective